MODUL BAGI GURU: PENANGANAN PERILAKU MENGGANGGU SISWA DI KELAS - Patty, Florenta Giovenda (University of Surabaya, 2016)
Purpose of this study is to equip teachers with guideline to improve the knowledge and understanding about studentâs disruptive behavior and its treatments. The guideline realized in module. Five teachers were included as participant. Observation and interview were conducted to determine the knowledge and understanding about studentâs disruptive behavior and the treatments. The collected data showed that the teachers still do not fully understand the disruptive behavior of students, teachers just focus on the termination of studentâs disruptive behavior, teachers have not been able to control studentâs behavior at the interval time, do not involve studentâs self-control also do not involve parents. This module discuss studentâs disruptive behavior, behavior management, studentâs self-control also parents involvement. The evaluation showed that the module could increases knowledge and understanding of treatments for handling studentâs disruptive behavior involves students and parents.